Bay Tat Rika's Entrepreneurial Intention In The Governor's Patang Of Bengkulu City - Huda, Okta Nurul; Anzori, Anzori; Yustanti, Nirta Vera (Jurnal Fokus Manajemen, 2026)
This study aims to describe the Entrepreneurial Intention of Bay Tat Rika in Pematang Gubernur, Bengkulu City. This study uses qualitative research. Qualitative research is a research method used to examine natural object conditions, where the researcher is the key instrument and the results of qualitative research emphasize more on meaning. The type of this research is descriptive qualitative. The results of this study are a small and medium enterprise engaged in the production of traditional cakes. Bay Tat Rika produces traditional cakes using quality ingredients. The production process is carried out manually using simple equipment. Good and consistent product quality makes Bay Tat Rika a consumer choice. Bay Tat Rika uses online marketing strategies to increase sales and expand market reach. Online marketing is carried out through social media such as Instagram and Facebook. Bay Tat Rika also collaborates with shops and cafes in Pematang Gubernur, Bengkulu City to increase sales.